Identification of physical interaction between trimethoprim and sulfamethoxazole by contact method koflerand crystallization reaction - Erizal Zaini; Yeyet C. Sumirtapura; Sundani N. Soewandhi; Auzal Halim (Indonesian Journal of Pharmacy, 2010)
Identification  of  solid  state  interaction  between  TMP  and  SMZ  by  hot contact  method Kofler and  crystallization  reaction  had  been  carried  out.  The results of hot contact method Koflershown formation a new crystalline habit as long  and thin needle  shaped  on  contact  zone  (mixing  zone) between Solid  TMP and SMZ. It had a different melting point in compared to its single component. Crystallization  reaction  between  two  of  supersaturated  solution  of  component TMP and  SMZ  in methanol  solvent  also  indicated  the  growth  of crystal  habit  as similar as   hot contact method Kofler.  Solid  state  interaction between  TMP  and SMZ  was confirmed  by  microscopic  SEM, powder  X-ray diffraction,  and  thermal DSC.  Microscopic  analysis by  SEM  showed significantly  the  change  of habit and morphology  of   crystal  as  long  and  thin  needle  shaped.  New  powder  X-ray diffraction  (PXRD)  interferences  peaks  were  observed  in  addition  to  PXRD interference  peaks  of  each  component  that  proved  formation  of  cocrystalline phase.  Thermogram  DSC  indicated  a  new   endothermic  peak  corresponding  to melting point of a new cocrystalline phase at temperature 178,82 °C.Key words : trimethoprim, sulfamethoxazole, physical interaction, cocrystalline phase